Toward a Robust Fiscal Framework for Iceland : Motivation and Practical Suggestions - Annett, Anthony (IMF Working Papers; Working Paper ;, 2007)
Expenditure in Iceland, especially related to the government wage bill, has tended to move in a procyclical manner, related to the fragmentation of political decision making. Iceland's elevated macroeconomic volatility reinforces these tendencies, as large booms unleash greater fiscal pressures as well as procyclical revenue elasticities that magnify these underlying strains. To improve its fiscal framework, Iceland could look to the experience of countries like Belgium and the Netherlands. In particular, it could adopt binding nominal expenditure rules, independent forecasts, and use representative committees to lay out medium-term targets across different levels of government.